Caps on Political Lobbying: Reply - Che, Yeon-Koo; Gale, Ian L (American Economic Review, 2006)
Yeon-Koo Che and Ian Gale (1998) studied the impact of imposing a cap on lobbying expenditures. They showed that a cap may lead to (1) greater expected aggregate expenditures and (2) a less efficient allocation of a political prize. In their comment, Todd Kaplan and David Wettstein (2005) show that if the cap is not rigid (i.e., its effect on the cost of lobbying is continuous) it has no effect.